Conclusions and policy implications [In Agricultural Extension] - Davis, Kristin E.; Babu, Suresh Chandra; Ragasa, Catherine (International Food Policy Research Institute, 2020)
The two objectives of this book are to assess extension and advisory services in a cross-country comparative context in the following ways: 1. Provide a description and comparison of the existing extension services in the regions and countries under consideration focused on a set of characteristics; and 2. Provide an assessment of the performance of extension services provision and impact evaluation of extension approaches in selected case study countries. Objective 1 addresses specific extension characteristics from the best-fit framework that include governance structures, capacity, management, and advisory methods. Part 1 offers a global overview based on primary data as well as regional and country cases based on primary and secondary data. Objective 2 undertakes in-depth country-level case studies based on primary and secondary data (Part 2). The best-fit conceptual framework allows some comparability of selected characteristics and results across geographies. The book generates specific policy recommendations that will be of use to government agencies, development partners, academics, and coordinating bodies for agricultural extension services. With the best-fit framework that allows for comparative analysis of selected characteristics (governance structures, capacity, management, and advisory methods), the book also demonstrates the process of extension system assessment through country-level case studies.